2017
DOI: 10.1007/s00520-017-3692-x
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations, outcomes, and management costs of febrile neutropenia in patients from a managed care population

Abstract: Purpose The study objective was to evaluate chemotherapy treatment patterns and incidence, cost, and resource utilization of febrile neutropenia-related hospitalization (FNH) in patients with breast cancer, lung cancer, and non-Hodgkin’s lymphoma (NHL) from Kaiser Permanente Southern California (KPSC), a large integrated delivery system. Methods Adults ≥18 years with any stage breast cancer, lung cancer, or NHL who initiated myelosuppressive chemotherapy from 01/01/2006 to 12/31/2009 were included. Chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 24 publications
6
43
0
1
Order By: Relevance
“…The aggressive care administered resulted in an average hospital LOS of five days and receipt of broad-spectrum antimicrobial therapy, both of which have a significant impact on healthcare costs and put the patient at risk for adverse events. 4,15,16 Our study findings are consistent with a previous study that reported a 98% non-adherence rate in low-risk patients resulting in a median hospital LOS of four days. 11 Additionally, they found a high adherence rate in those deemed high risk.…”
Section: Discussionsupporting
confidence: 91%
“…The aggressive care administered resulted in an average hospital LOS of five days and receipt of broad-spectrum antimicrobial therapy, both of which have a significant impact on healthcare costs and put the patient at risk for adverse events. 4,15,16 Our study findings are consistent with a previous study that reported a 98% non-adherence rate in low-risk patients resulting in a median hospital LOS of four days. 11 Additionally, they found a high adherence rate in those deemed high risk.…”
Section: Discussionsupporting
confidence: 91%
“…Exercise can be considered an effective, multifaceted, supportive therapy to achieve these goals. Febrile neutropenia is a common toxicity with myelosuppressive chemotherapy that is associated with substantial morbidity, mortality, and cost . The 13% rate of hospitalization for febrile neutropenia reported in the OptiTrain usual care group was similar to that (13.9%) recently reported in a database analysis of 3,314 patients with breast cancer .…”
supporting
confidence: 72%
“…Febrile neutropenia is a common toxicity with myelosuppressive chemotherapy that is associated with substantial morbidity, mortality, and cost . The 13% rate of hospitalization for febrile neutropenia reported in the OptiTrain usual care group was similar to that (13.9%) recently reported in a database analysis of 3,314 patients with breast cancer . Importantly, the RT‐HIIT OptiTrain intervention significantly reduced hospitalization rates to 3% of patients and also reduced incidence of thrombocytopenia, a less common toxicity that can also increase health care costs.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…Febrile neutropenia (FN) is common with chemotherapeutic agents and considered one of the oncologic emergencies [1, 2]. It is associated with a major increase in morbidity and mortality, healthcare resource use, and compromise efficacy of chemotherapy [24]. Granulocyte colony-stimulating factor (G-CSF) has been shown to reduce the duration and severity of neutropenia and the risk of febrile neutropenia and enable delivery of full dose-dense chemotherapy when indicated [57].…”
Section: Introductionmentioning
confidence: 99%